GEOGRAPHY LEARNING DESCRIPTION REVIEWED FROM OPENNESS PERSONALITY STUDENTS OF MAN I MEDAN - Siti Aisyah; Suryani Hardjo (Universitas Negeri Medan, 2022)
The purpose of this study was to find out the description of geography learning in terms of the open personality of the students of MAN I Medan. This type of research is descriptive and quantitative. The sample in this study was the entire subject population, namely all 61 students consisting of two classes. The data collection technique was carried out by distributing a questionnaire (questionnaire) to respondents, which contained questions about the open personality of students and the geography learning experienced so far in the learning process. The descriptive percentage data analysis technique is intended to determine the status of variables, namely, to describe openness personality in geography learning. This study found that learning geography can put students in contact with their geographical environment to better understand modern processes and problems. The strongest openness personality of the MAN I Medan students is curiosity, while the lowest openness personality is smart and thinking. Curiosity is an action that always seeks to know deeper or wider than something learned, seen, and heard. Therefore, it is necessary to provide freedom by explaining the learning encyclopedia to develop and accommodate students' curiosity. This happens due to differences in all student’s abilities and personalities. Personality and ability are dimensions of individual differences in the tendency to exhibit consistent patterns of thinking, feeling, and acting. The nature of the personality focuses on identifying, describing, and measuring individual differences and is also a behavioral and mental mark typical of individuals who refer to differences through feelings, emotions, actions, motivations, and behaviors.Keywords: Geography, Openness Personality, Students